Greece : Third Review Under the Extended Arrangement Under the Extended Fund Facility-Staff Report; Staff Statement; Press Release; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report, 2013)
The short-term objectives are being met, but medium-term targets and sustainability have to be worked on. The impressive fiscal adjustment evident since the crisis erupted is continuing. The Executive Directors commend the Greek government's determination to focus on overdue spending cuts. However, progress on improving tax administration and public administration reforms needs to be started in earnest. There is concern about debt relief undermining the payment culture. Reforms to open up the economy to competition should be stepped up. The macroeconomic and debt outlook must remain under close review.